Pengaruh Pembinaan Disiplin dan Keselamatan dan Kesehatan Kerja (K3) terhadap Kepuasan Kerja Karyawan Divisi Stamping Bagian Produksi-1 PT. Xyz - Sera Ambarwati; R.M. Juddy Prabowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of discipline coaching and occupational safety and health (K3) on employee job satisfaction in the Stamping Division of Production Section-1 of PT. XYZ. The approach used is quantitative by distributing questionnaires to 76 employees who have worked for at least one year. Data measurement uses a semantic differential scale, and analysis is carried out through validity, reliability, multiple linear regression, coefficient of determination, and partial tests. The results of the study indicate that all instruments are valid (r_count > r_table 0.1901) and reliable (Cronbach's Alpha > 0.60). Descriptively, discipline coaching is in the